Ecchymosis and Coldness in Peripheral Varicose Vein Patients: Observations From VEIN-TURKEY Study. (September 2020) - Ozturk, Selcuk; Akbaba, Kagan Turker; Kilic, Suleyman; Cicek, Tufan; Peskircioglu, Levent; Tandogan, Izzet; Gurlek, Ahmet; Aydemir, Ozbay; Ileri, Mehmet; Yetkin, Ertan
The purpose of this subgroup analysis is to investigate and analyze the venous leg symptoms including sense of coldness and sign of ecchymosis in patients with or without peripheral varicose veins (PVVs) from VEIN-TURKEY study population. A total of 600 patients, who were enrolled to VEIN-TURKEY study recently, were included in this subgroup analysis. Patients were examined clinically for the presence and severity of PVV and varicocele. Patients were asked to answer the VEINES-Sym questionnaire consisting of 10 parts and questions about ecchymosis and coldness in their legs. Frequency of symptoms present in the VEINES-Sym instrument, coldness (16.6%, 6.5%, P = .002, respectively), and ecchymosis (16.6%, 2.7%, P < .001, respectively) were significantly higher in patients with PVV compared to patients without PVV. Mean score of each symptom was significantly lower in PVV (+) patients including scores of ecchymosis and coldness. Total VEINES-Sym score was also correlated with the scores of ecchymosis ( r = 0.18, P < .001) and coldness ( r = 0.35, P < .001). Logistic regression analysis revealed that heavy legs, aching legs, night cramps, and ecchymosis are significantly and independently associated with PVV. In conclusion, sign of ecchymosis and coldness are significantly higher in patients with PVV compared to patients without PVV in a population recruited from the urology clinics. In clinical evaluation, presence or sign of ecchymosis and coldness in legs should be considered to be compatible with PVV in the absence of trauma, hematologic pathologies including antiplatelet treatment, and arterial stenosis or obstruction.